(untitled) (Comprehensive Journal of Science, 2026)
This study was conducted with students from the College of Education in Derj to determine their perceptions regarding tests and the criteria for an effective test. The study focused on students’ perspectives due to their diverse experiences and ideas about examinations. A questionnaire was administered to undergraduate students, and SPSS was used to analyze the responses received. The results indicated that most students prefer questions that are simple and easy to comprehend. Students found it easier to take tests when the questions were clear and concise. Students also emphasized the need for fairness and believed that tests should be based on the material that was actually taught in class. Some students also stated that quizzes and homework were more important than just taking final examinations. Additionally, some participants reported that exam-related stress negatively affected their performance. In general, students preferred tests that helped them learn better rather than tests that focused only on achieving grades.